Analysis and Design of Information Systems for Lecturer Performance Reports at Jambi Muhammadiyah University - Kurniawansyah, Kevin; Marthiawati. H, Noneng; Sari, Anita Puspita (Fakultas Sains dan Teknologi, Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
In a tertiary institution, the existence of lecturers is needed to carry out the tridharma activities of higher education and it is the responsibility of the lecturers themselves. Higher Education Tridharma covers Education, Research and Service. There are several problems that researchers see related to the performance of lecturers, especially for the University of Muhammadiyah Jambi Higher Education. So far, the processing of lecturer performance data at the University of Muhammadiyah Jambi is carried out conventionally, namely inputting data into Microsoft Excel by the admin on duty and additional files that have been submitted by each lecturer are simply stored on the computer without a data center or centralized data storage. . The purpose of this study is to analyze and design a lecturer performance report information system that is able to simplify business processes, use lecturer performance reports according to needs and process lecturer performance data which includes identity data, lecturer tridharma data, and other supporting data more effectively and efficiently by system prototyping method that produces a web-based lecturer performance report information system at the Muhammadiyah University of Jambi to overcome existing problems